CREATIVE TRENDS OF THE DOUBLE TRANSITION OF FASHION INDUSTRY ENTERPRISES UNDER MARTIAL LAW IN UKRAINE - Бондаренко, Світлана М. (Journal of Strategic Economic Research, 2026)
During the martial law, the importance of fashion industry as a sphere of economic activity is growing. The enterprises of the industry are experiencing significant difficulties caused by military aggression, problems with energy supply, world turbulence and cardinal changes in domestic and foreign markets. the industry is also experiencing positive developments caused by the active development of digitalization and environmentalization. In order to survive and prosper, fashion industry enterprises need a double transition, which involves digital and green transformation. The purpose of the study is to substantiate the need for a double transition of enterprises in the fashion industry to digital and green leadership, which involves the formation of creative trends and the use of modern creative technologies based on sustainable development and digitalization. A complex of general scientific methods was used, in particular, system analysis and synthesis, logical methods of cognition, as well as methods of generalization, induction and deduction. The need for a dual transition of Ukrainian fashion industry enterprises to digital and green leadership is substantiated, which involves the formation of creative trends and the use of modern creative technologies based on sustainable development and digitalization. The creative technologies used in fashion industry enterprises are characterized. In conditions of martial law, fashion industry acquires special strategic importance, as it provides the Armed Forces of Ukraine and other law enforcement agencies with uniforms, contributes to the preservation of jobs and replenishment of the state budget. The study showed that under current operating conditions in Ukraine, fashion industry enterprises need to make a double transition and combine environmentally friendly development with digital transformation of business processes in order to maintain competitiveness and sustainable development. The double transition ensures the combination of digitalization with environmental, social and economic goals of fashion industry enterprises. Creativity has become the driver of new trends that allow enterprises not only to remain competitive, but also to shape global trends. Trends stimulate the development of creative technologies. Creative technologies provide the means and form of implementation of creative trends. Creative trends and creative technologies are closely interconnected and together form innovative products that meet the expectations of modern stakeholders.